Tiếp cận định lượng trong nghiên cứu địa lý và ứng dụng - Huần, Nguyễn Cao; Thịnh, Nguyễn An (Vietnam Journal of Earth Sciences, 2005)
The article deals with quantitative approach in geographical research : the concepts, opinions, priority and disadvantage, classification of mathematic models in Geography. This approach with using factor analysis is applied in an evaluating suitability of land units for cotton crop in Dak Lak province. The analysis process includes Standardizing original data model, Correlation analysis model, Factor analysis models (principal component analysis model, principal factor analysis model, varlmax rotation model and data orthogonally model). In the territorry of four districs : Cu Jut, Buon Don, Cu M'Gar, Krong Ana and Buon Ma Thuot town of Dak Lak province, the results of evaluation show that in the investigated area there are about 121,67 4 ha (30.6% total area) suitable for cotton crop.